Thermodynamic study of the solubility of ibuprofen in acetone and dichloromethane - Diana Marcela Aragón; Jaiver Eduardo Rosas; Fleming Martínez (Universidade de São Paulo, 2010)
Thermodynamic functions, Gibbs energy, enthalpy and entropy for the solution processes of ibuprofen (IBP) in acetone and dichloromethane (DCM) were calculated from solubility values obtained at temperatures ranging from 293.15 K to 313.15 K. The respective thermodynamic functions for mixing and solvation processes as well as the activity coefficients for the solute were calculated. IBP solubility was high and proved similar in both solvents but was greater in DCM than acetone. In addition, the thermodynamic quantities for the transfer process of this drug from cyclohexane to the organic solvents were also calculated in order to estimate the contributions of hydrogen-bonds or of other dipolar interactions. The results were discussed in terms of solute-solvent interactions. As funções termodinâmicas, energia de Gibbs, entalpia e entropia dos processos de solução de ibuprofeno (IBP) em acetona e em diclorometano (DCM) foram calculadas a partir dos valores de solubilidade, obtidos em intervalos de temperatura de 293,15 K a 313,15 K. As funções termodinâmicas respectivas para os processos de mistura e solvatação e os coeficientes de atividade para o soluto também foram calculados. A solubilidade do IBP foi grande e semelhante em ambos os solventes, mas, maior em DCM do que em acetona. Em adição, as quantidades termodinâmicas relativas ao processo de transferência desse fármaco do cicloexano para os solventes orgânicos foram, também, calculadas com o objetivo de estimar as contribuições devidas às ligações de hidrogênio ou a outras interações dipolares. Os resultados foram discutidos nos termos das interações soluto-solvente.